Throwback, trials, and triumphs: stories of unmarried retired Filipina Public School teachers - Bolo, Ma. Nita; Singson, Deborah Natalia (Technium Social Sciences Journal, 2023)
Background: Globally, there is an apparent demographic movement toward an aging population. This poses difficulties, especially for retired public school teachers who are single. Additionally, the researcher, who has spent years offering psychosocial services to clients, is aware of this group's susceptibility to aging-related difficulties that may jeopardize their well-being. Methods: A qualitative-phenomenological approach was adopted. In-depth semi-structured interviews were conducted with 6 participants aged 60 to 80, unmarried retired public school teachers. Employing thematic analysis, interview transcripts were analyzed for themes to organize the data. Results: Four major themes emerged: (1) Embracing a Positive Emotional State, with Sub-themes (a) Awakening of reality being single for life, (b) Maintaining a smooth interpersonal relationship, (c)Achieving a sense of meaning, (2) Confronting the challenges with Sub-themes (a) Dependency of family members (b)Managing financial needs (c) Coming to terms with death (3) Coping With Life Eventualities with Sub-themes (a) Staying productive (b) Participating in Civic and Religious Organizations (c) Connecting with God (4) Breaking stereotypes about being a spinster teacher and ageism. Conclusion: Aging vulnerabilities can particularly challenge those who live without a spouse. However, having a hopeful, positive attitude about the future helps the unmarried remain motivated to cope with life. Ultimately, this will bring the elderly to resiliency and acceptance. Their experiences can add to a growing study in developmental psychology and personality that looks at how life accounts reveal the inherent aspects of lived human experience. The outcome of the past, the wisdom behind the trials, and the success stories of the life of participants were essential for understanding the strategies they use to manage age and aging-related challenges and age successfully. Limitations of the findings: The scope was limited to Northern Negros area while the number of participants in this study was within the acceptable range of six (6). The participants were all female and all were teachers from the public school system. Thus, the findings are not conclusive, and this limitation made it difficult to explore their experiences within the broader context of their lives. Direction for Future Research: Future research can be built upon the results that were acquired in this study. Further research could also be done on effective preventative and therapeutic strategies for elderly single people. It is advised to conduct additional research using more extensive samples of this demographic that is to include single male retired public and private school teachers. A longitudinal study might provide a more comprehensive and in-depth view of aging and spinsterhood. Examining the extended family's perspectives, other professions, and the larger population is an aspect that could help broaden and deepen the understanding of the experiences of single and retired teachers. Practical Value of the Paper: The findings will serve as baseline data for improving interventions and programs of DepEd and OSCA, which must concentrate on offering practical assistance, like psychosocial services and a solution for social acceptance, to eradicate stigma. Mental health professionals must have knowledge and guidance on how to facilitate the well-being of the elderly and enhance their quality of life as they age.